Granville Island 2040: More Walkable and Even More Vibrant (breakout presentation). (December 2017) - Mueller, Simon; Wilson, Thea; Phillips, Brian; Joyce, Peter; Lippa, Sebastian
Abstract : Background: Bunt & Associates, commissioned by the Canada Mortgage and Housing Corporation (CMHC), recently engaged in a transportation planning study as part of a broader visioning process (GI2040) to reinvigorate the culturally and economically significant district of Granville Island located in the heart of the City of Vancouver. While Granville Island enjoys a relatively walkable environment, issues persist. Access by walking and other multimodal options remain a challenge, resulting in a considerable amount of vehicle trips continuing to access the area. By improving multimodal access options, there is an enticing opportunity to repurpose some existing parking areas and further foster a more walkable and accessible realm, while ensuring continued viability of Granville Island's many unique uses. Aim: The goal of the transportation planning component of the GI2040 project was to determine how walk, bicycle, and transit accessibility to Granville Island could be improved and to provide a bold and workable transportation plan to bring the vision for a more walkable Granville Island to reality. Method: The project involved an extensive data collection program, which mirrored a similar program undertaken by Bunt & Associates 10 years earlier. This data provided the basis for a detailed evaluation of current travel mode share and trip profiles and how these have changed over time. As well, multimodal accessibility analyses using GIS and time dependent transportation network characteristics (including innovative integration of TransLink GTFS data) was utilized to assess the benefits of improved walking and multimodal connections to Granville Island. Results: The impacts to multimodal travel time accessibility were quantified in terms of the number of people within a certain travel time to Granville Island and how infrastructure improvement options would influence their likelihood to choose to walk, bicycle, or take transit. Given these access improvements, it was determined that repurposing space currently used for vehicular mobility and parking would not negatively impact the amount of people accessing Granville Island. Conclusions: The Granville Island 2040 Transportation Plan identifies several well-supported and unique infrastructure improvements intended to encourage more walking and multimodal access, and to facilitate the transition to an even more vibrant and walkable district.